Relationship between Profile of Rural Youth and Attitude towards Agriculture (Indian Journal of Extension Education, 2021)
The study was conducted in Hisar and Bhiwani districts of Haryana, with an objective to analyze the relationship between profile characteristics of rural youth with their attitude towards agriculture. Empirical data were collected personally from 192 respondents comprising 12 rural youth from sixteen villages through a structured interview schedule and analyzed using standard methodology. Findings revealed that 72.39 per cent possessed a less favorable to favorable attitude towards agriculture. The correlation and regression analysis of different variables i.e. occupation, income expectancy, comfort expectancy, affiliation expectancy exhibited positive and significant effect, whereas age, educational status, non-farm skill, proximity to towns and cities, prior migration experience, economic motivation, risk orientation, self-reliance and self-confidence exhibited negative and significant effect. However, farm skills and achievement motivation exhibited non-significant effect but positively correlated with their attitude towards agriculture. Hence, the paper recommends that there is a need of special efforts to attract, train and retain the rural youth in agriculture as a whole by developing more favorable attitude towards agriculture by transforming and making it more agribusiness oriented, scientifically attractive and economically profitable.